Occurrence of Antimicrobial Resistance in Hospital: A Systematic Review and Meta-analysis - ยิ่งขจร, สุพรรณี; สุทธิโชติ, สตา; หงส์ทอง, นิธิกุล; บุญรอด, ตั้ม; สิมลา, วิชชาดา; ศรีรักษา, ศิริรัตน์ (Journal of Health Science of Thailand, 2021)
Antimicrobial resistance is a worldwide problem for public health. The occurrence of antimicrobial resistance is varied and different in each region. The World Health Organization estimated that the number of deaths due to antimicrobial resistance worldwide would be over 700,000 in 2014 and 10 million in 2050. Nine million cases of antimicrobial resistance were reported in Asia and Africa regions; and equired 3,500 trillion Bath for treatment. Hence, the antimicrobial resistance should be closely investigated subsequent and monitored. This study aimed to conduct a systematic review with meta-analysis based on the PRISMA guidelines by analysing the articles published between 2009-2019 from PubMed, Science Direct, Web of Science, Google Scholar and ThaiJo. As for the results, there were 21 articles reported both Gram-negative bacteria and Gram-positive bacteria with antibiotic resistance in the hospitals. The Gram-negative bacteria were Escherichia coli, 20.00% (95%CI=17.00-22.00), Klebsiella pneumonia, 12.00% (95%CI=10.00–13.00), Pseudomonas aeruginosa, 8.00% (95%CI=6.00–10.00), Acinetobacter baumannii, 4.00% (95%CI=4.00–5.00); and the Gram-positive bacteria was Staphylococcus aureus, 6.00% (95%CI=5.00–8.00). Findings from this systematic review indicated the need for hospitals and health officials to pay more attention on this issue; and to promote effective strategy and policy for the prevention and control of antimicrobial resistance.